Pelatihan Dan Pendampingan UMKM Dalam Optimalisasi Digital Marketing Melalui Instagram Sebagai Upaya Pengembangan UMKM - Tiska Khoirotun Nisa; Riko Setya Wijaya; M. Taufiq (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
Digital marketing is a marketing medium that uses the internet as a tool to disseminate information in a wider range without being hindered by time, place and distance. And Instagram is one of the digital media which is still widely used by Indonesians, from teenagers to adults, both for communication media and promotional media. However, most MSMEs actors in the Kedung Baruk sub-district have not been able to make full use of Instagram even though they already have it. So the purpose of holding this training and mentoring is so that MSMEs understand the importance of digital marketing, and optimizing Instagram as a promotional medium. The method used goes through several stages such as providing digital marketing training, providing assistance, and conducting evaluations. The results obtained from the activities that have been carried out are that UMKM actors realize how important digital marketing is, especially on the Instagram platform and Pempek D&G have been able to optimize Instagram as a promotional medium independently.